2015
DOI: 10.1111/jgs.13656
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Services for Complicated Grief and Depression: Results from a National Survey

Abstract: OBJECTIVES To describe the prevalence of screening for complicated grief (CG) and depression in hospice and access to bereavement therapy and to examine whether screening and access to therapy varied according to hospice organizational characteristics or staff training and involvement. DESIGN Cross-sectional national survey conducted from 2008 to 2009. SETTING United States. PARTICIPANTS Hospices (N = 591). MEASUREMENTS Whether hospices screened for depression or CG at the time of death or provided acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…These findings are consistent with previous hospicebased studies, which found that about one-third of all bereaved family members or friends utilize hospice bereavement services 24,33 and that less than half of those with symptoms of CG or depression do so. 17,24 These findings are also consistent with broader trends in mental health care, which indicate that the majority of Americans with any type of mental health symptoms do not utilize support from mental health professionals. 34,35 Although reasons for low interest in bereavement services remain unknown and could not be explored in the current analyses, some factors that have been identified in previous research include not thinking participation would be helpful, and not wanting to seek support outside family members or friends.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These findings are consistent with previous hospicebased studies, which found that about one-third of all bereaved family members or friends utilize hospice bereavement services 24,33 and that less than half of those with symptoms of CG or depression do so. 17,24 These findings are also consistent with broader trends in mental health care, which indicate that the majority of Americans with any type of mental health symptoms do not utilize support from mental health professionals. 34,35 Although reasons for low interest in bereavement services remain unknown and could not be explored in the current analyses, some factors that have been identified in previous research include not thinking participation would be helpful, and not wanting to seek support outside family members or friends.…”
Section: Discussionsupporting
confidence: 69%
“…National survey data indicate that 92% of hospices screen family members/friends for depression or CG at some point after the hospice patient is admitted and 69% screen at the time of the patient’s death, and that 79% provide group or individual therapy. 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While little research has been done regarding this transition, ICs in this review suggested initiating bereavement visits performed by members of their current interdisciplinary team. As bereavement services are only used by a fraction of ICs, 67 encouraging the IC's team of hospice providers to aid in the transition to bereavement services after the death of the patient could improve the delivery of this important aspect of care.…”
Section: Discussionmentioning
confidence: 99%
“…CG and depression are both associated with a number of negative outcomes, including hypertension, sleep impairment, and suicidal ideation (Stroebe, Schut, & Stroebe, 2007). Data from a recent national survey found that 92% of U.S. hospice provide screening for depression, 97% provide screening for CG, and 79% provide either group or individual psychotherapy (Ghesquiere et al., 2015), but little data exist on the details of hospice practices in this arena.…”
Section: Introductionmentioning
confidence: 99%